Exploring Chemistry Teacher’s TPCK in Rasch Model: A Point of View from Difference of Teaching Stage, Gender, and Ages. - Inas Sausan; Jamaludin; Elda Frediana Rety Kartika; Dola Suciana; Sukma Wahyu Wijayanti (Jurnal Penelitian Pendidikan IPA, 2023)
Teachers should have different knowledge types including technological, pedagogical, and content to realize effective learning in the digital era. Technological Pedagogical and Content Knowledge (TPCK) is a framework that explains these knowledge types and the interactions between them. It is considered to enable chemistry teachers’ multifaceted teaching. Coping, for this reason, a study to examine chemistry teachers’ level of TPCK is needed. This paper reports the level of chemistry teacher’s TPCK and their perception in terms of teaching stage, gender, and age. The study involved fifty-three students of chemistry education in a public university in Indonesia. A quantitative method was applied to explore their perspective on TPCK. Data were collected through surveys and interviews. The findings showed that the majority of chemistry teachers’ TPCK skills are currently good. They integrate technology into their teaching while conducting online learning due to the COVID-19 pandemic. In terms of teaching stage, age, and gender, provide deep insight into seven indicators of TPCK. However, some indicators still need to be improved, so a TPCK training program for individuals or centralized individuals should be added to the chemistry department program.